2020
DOI: 10.7150/thno.45035
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen carrier in core-shell fibers synthesized by coaxial electrospinning enhances Schwann cell survival and nerve regeneration

Abstract: Rationale: Local hypoxia is a challenge for fabrication of cellular grafts and treatment of peripheral nerve injury. In our previous studies, we demonstrated that perfluorotributylamine (PFTBA) could provide short term oxygen supply to Schwann cells (SCs) and counteract the detrimental effects of hypoxia on SCs during the early stages of nerve injury. However, the quick release of oxygen in PFTBA compromised its ability to counteract hypoxia over an extended time, limiting its performance in periphe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 61 publications
(71 reference statements)
0
36
0
Order By: Relevance
“…They observed a significantly greater survival of GFP labeled SCs within the PFTBA conduit up to 28 days after implantation as compared to the conduit with SCs but without the hydrogel. In Ma et al (2020), the authors demonstrated further enhancement of SC survival in a conduit designed with a core-shell structure containing encapsulated PFTBA. The new scaffold coupled with the PFTBA hydrogel allowed for greater oxygen carrying capacity and increased SC survival during the initial hypoxic phase of nerve regeneration.…”
Section: Sc Adherence and Survival In Conduit Tubesmentioning
confidence: 97%
See 2 more Smart Citations
“…They observed a significantly greater survival of GFP labeled SCs within the PFTBA conduit up to 28 days after implantation as compared to the conduit with SCs but without the hydrogel. In Ma et al (2020), the authors demonstrated further enhancement of SC survival in a conduit designed with a core-shell structure containing encapsulated PFTBA. The new scaffold coupled with the PFTBA hydrogel allowed for greater oxygen carrying capacity and increased SC survival during the initial hypoxic phase of nerve regeneration.…”
Section: Sc Adherence and Survival In Conduit Tubesmentioning
confidence: 97%
“…There were 15 studies (Aszmann et al, 2008;Sun et al, 2009;McGrath et al, 2010;Berrocal et al, 2013;Jesuraj et al, 2014;Hoben et al, 2015;Liu et al, 2017;Wang et al, 2017;Gonzalez-Perez et al, 2018;Ma et al, 2018Ma et al, , 2020Huang et al, 2019;Burks et al, 2021;Yao et al, 2021) that evaluated the number of myelinated axons within the graft through light microscopy and/or through immunostaining. Among those, 14 studies demonstrated significant improvement in myelinated axon counts in the graft with SCs as compared to the graft alone (Aszmann et al, 2008;Sun et al, 2009;McGrath et al, 2010;Berrocal et al, 2013;Jesuraj et al, 2014;Hoben et al, 2015;Liu et al, 2017;Wang et al, 2017;Gonzalez-Perez et al, 2018;Ma et al, 2018Ma et al, , 2020Huang et al, 2019;Burks et al, 2021;Yao et al, 2021). The presence of regenerated myelinated axons in the middle of a 10-mm gap were observed as early as 10-14 days after surgery (Huang et al, 2019;Yao et al, 2021) and in the distal end of a 10-mm gap as early as 3-4 weeks (McGrath et al, 2010;Liu et al, 2017;Huang et al, 2019).…”
Section: Improvement In Myelinated Axonsmentioning
confidence: 99%
See 1 more Smart Citation
“…The ever-increasing process understanding in this remit has enabled the ES process to evolve, yielding complex and innovative systems; including coaxial systems containing multiple concentrically arranged needles (yielding multi-layered fibers) [186,[219][220][221][222][223][224][225][226][227][228][229][230][231][232][233] and electrohydrodynamic printing [2,57,142,[234][235][236][237][238][239][240][241]; enabling the fabrication of prepatterned, aligned fibers. An emerging development includes systems utilising a needleless approach; yielding fibers within the nanometer range without the use of a conductive nozzle [242][243][244][245][246][247][248][249][250][251].…”
Section: Electrospinning Process and Set-upmentioning
confidence: 99%
“…Whilst there are many advantages to current polymeric biomedical implants, they do not possess the ability to provide sufficient contrasting for imaging and theranostics. These limitations have been overcome by incorporating contrasting agents or markers into electrospun fibrous matrices [220]. By incorporating magnetic complexations or actives, the resulting fibrous systems can be spatiotemporally controlled via a magnetic field which is operated externally [408].…”
Section: Theranosticsmentioning
confidence: 99%